Microbiological investigation (qPCR) on sediment samples from thermokarst terrain in the continuous permafrost zone of Arctic Alaska - Seemann, Fabian; Liebner, Susanne; Saborowski, Anke; Jenrich, Maren; Strauss, Jens (PANGAEA, 2025)
We investigated microbiological structures by conducting quantitative Polymerase Chain Reaction (qPCR) analyses on sediment samples from thermokarst terrain in the continuous permafrost zone of Arctic Alaska. Sediment cores from undisturbed tundra uplands, thermokarst lakes and drained lake basins were taken in the field in April 2022 (Barrow Peninsula) and March 2024 (Baldwin Peninsula). Samples were kept frozen until microbiological subsampling and subsequent analyses took place. Laboratory work was conducted at the GFZ Helmholtz Centre for Geosciences Section Geomicrobiology (Potsdam, Germany). During subsampling, 1.5 g wet sample was filled into Eppendorf vials. Until laboratory work started, these samples were stored frozen at -30 °C. Total nucleic acids were extracted in duplicate using the DNeasy PowerSoil Pro Kit (Qiagen, Germany) according to the manufacturer's instructions. DNA extracts were subsequently purified with the DNA Clean & Concentrator-25 Kit (Zymo Research, USA). Bacterial abundance was estimated via quantitative PCR (qPCR) targeting the 16S rRNA gene, as well as the functional genes pmoA (methane oxidizers), mcrA (methane producers), and dsrB (sulfate reducers). Each qPCR reaction (20 µl) consisted of 2× SensiFAST SYBR Mix (Kapa Biosystems, Wilmington, USA) and 100 µM of each primer (Microsynth AG, Germany). Standard curves were generated from serial 1:10 dilutions of templates with known gene copy numbers, producing five standards that were analyzed in triplicate alongside the samples. A negative control containing PCR-grade water was included in each run. The qPCR amplification was conducted on a Bio-Rad CFX Connect system. A melting curve analysis was performed at the end of each run to verify product specificity and overall assay quality.
Keywords: methanogens; methanotrophs; microbial abundance; qPCR; sediment; Sulfate reducing bacteria; thermokarst